State of Art for Semantic Analysis of Natural Language Processing - Hussen Maulud, Dastan; Zeebaree, Subhi R. M.; Jacksi, Karwan; Mohammed Sadeeq, Mohammed A.; Hussein Sharif, Karzan (Qubahan Academic Journal, 2021)
Semantic analysis is an essential feature of the NLP approach. It indicates, in the appropriate format, the context of a sentence or paragraph. Semantics is about language significance study. The vocabulary used conveys the importance of the subject because of the interrelationship between linguistic classes. In this article, semantic interpretation is carried out in the area of Natural Language Processing. The findings suggest that the best-achieved accuracy of checked papers and those who relied on the Sentiment Analysis approach and the prediction error is minimal.